Strength training in endurance runners - Taipale, R. S.; Mikkola, J.; Nummela, A.; Vesterinen, V.; Capostagno, B.; Walker, S.; Gitonga, D.; Kraemer, W. J.; Häkkinen, K. (International Journal of Sports Medicine, 2010)
This study examined effects of periodized maximal versus explosive strength training and reduced strength training, combined with endurance training, on neuromuscular and endurance performance in recreational endurance runners. Subjects first completed 6 weeks of preparatory strength training. Then, groups of maximal strength (MAX, n=11), explosive strength (EXP, n=10) and circuit training (C, n=7) completed an 8-week strength training intervention, followed by 14 weeks of reduced strength training. Maximal strength (1RM) and muscle activation (EMG) of leg extensors, countermovement jump (CMJ), maximal oxygen uptake (VO2MAX), velocity at VO2MAX (vVO2MAX) running economy (RE) and basal serum hormones were measured. 1RM and CMJ improved (p<0.05) in all groups accompanied by increased EMG in MAX and EXP (p<0.05) during strength training. Minor changes occurred in VO2MAX, but vVO2MAX improved in all groups (p<0.05) and RE in EXP (p<0.05). During reduced strength training 1RM and EMG decreased in MAX (p<0.05) while vVO2MAX in MAX and EXP (p<0.05) and RE in MAX (p<0.01) improved. Serum testosterone and cortisol remained unaltered. Maximal or explosive strength training performed concurrently with endurance training was more effective in improving strength and neuromuscular performance and in enhancing vVO2MAX and RE in recreational endurance runners than concurrent circuit and endurance training.